2021
DOI: 10.1021/acs.est.1c00645
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the UV/Chlorine Process in the Disinfection of Pseudomonas aeruginosa: Efficiency and Mechanism

Abstract: UV irradiation and chlorination have been widely used for water disinfection. However, there are some limitations, such as the risk of generating viable but nonculturable bacteria and bacteria reactivation when using UV irradiation or chlorination alone. This study comprehensively evaluated the feasibility of the UV/chlorine process in drinking water disinfection, and Pseudomonas aeruginosa was selected as the target microorganism. The number of culturable cells was effectively reduced by more than 5 orders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 64 publications
3
70
0
Order By: Relevance
“…11 Here we report an additional 37 publications that have mechanisms including this loop. 51,64,65,[67][68][69][70][71][81][82][83]85,[87][88][89][90][92][93][94][95]97,[99][100][101][102][103][104][105][106][108][109][110][111][112][113]118,119 In our previous report we showed that correcting Loop ''D'' by supplying the requisite value for the reverse rate constant in the first step had no effect on the simulations of the overall mechanism in one of the publications. This outcome was traced to the fact that the first step could be eliminated entirely without affecting the results of the simulation.…”
Section: Subsequent Reports With Illegal Loopsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Here we report an additional 37 publications that have mechanisms including this loop. 51,64,65,[67][68][69][70][71][81][82][83]85,[87][88][89][90][92][93][94][95]97,[99][100][101][102][103][104][105][106][108][109][110][111][112][113]118,119 In our previous report we showed that correcting Loop ''D'' by supplying the requisite value for the reverse rate constant in the first step had no effect on the simulations of the overall mechanism in one of the publications. This outcome was traced to the fact that the first step could be eliminated entirely without affecting the results of the simulation.…”
Section: Subsequent Reports With Illegal Loopsmentioning
confidence: 99%
“…Two examples of published illegal loops involving HClOH˙ are discussed below. A total of 18 such illegal loops have been published, 10,18,20,21,23,26,27,30–33,35,39,40,46–118 and these are described in the ESI †…”
Section: Subsequent Reports With Illegal Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the measurement are listed in Test S5. Additionally, to examine bacterial metabolic activities, the integrated spectral intensities of the C–D band (2040–2300 cm –1 ) and the C–H band (2800–3100 cm –1 ) were used to quantify the degree of D substitution in C–H bonds, and the ratios between VBNC cell counts and dead cell counts could be represented by C–D/(C–H + C–D). ,, …”
Section: Experimental Sectionmentioning
confidence: 99%
“…Chlorination could completely inactivate bacteria, such as Escherichia coli and Enterococcus faecalis, but partially inactivate virus ( Tree et al, 2003 ). To guarantee the chlorination disinfection effect for bacteria and virus, especially for COVID-19, higher dose of chlorine and longer contact time were required ( Chu et al, 2021b ; Wang et al, 2020a , Wang et al, 2020b ), which could cause potential risk, such as generating viable but non-cultivable bacteria ( Wang et al, 2021 ). UV could also inactivate Escherichia coli and Enterococcus faecalis , but the bacteria could regrow after UV disinfection ( Li et al, 2017 ; Wen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%